2007
DOI: 10.1016/j.compcom.2007.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Weathering wikis: Net-based learning meets political science in a South African university

Abstract: Wikis represent flexible tools functioning as open-ended environments for collaboration while also offering process and group writing support. Here we focus on a project to innovate the use of wikis for collaborative writing within student groups in a final-year undergraduate political science course. The primary questions guiding our research were in what ways could wikis assist collaborative learning in an undergraduate course in political science and how we could support educators' in the effective use of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 19 publications
0
36
0
4
Order By: Relevance
“…Some studies support that Wiki is not user friendly and identify same issue as a cause of frustration among students and state that when another student uses same page, that may result in a loss of work [17]; frustration may occur due to lengthy participation [18]; technical problems [16]; 'unproductive interactions' 'threats to privacy' [19]; and discomfort in the assessment process [10,20]. Morley argues that the successful employment of Wiki requires careful guidance by the teacher as to how the Wiki works, or it may be helpful with face to face teaching combination to support students' learning [16].…”
Section: Category 2: Wiki Versus Google Docmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies support that Wiki is not user friendly and identify same issue as a cause of frustration among students and state that when another student uses same page, that may result in a loss of work [17]; frustration may occur due to lengthy participation [18]; technical problems [16]; 'unproductive interactions' 'threats to privacy' [19]; and discomfort in the assessment process [10,20]. Morley argues that the successful employment of Wiki requires careful guidance by the teacher as to how the Wiki works, or it may be helpful with face to face teaching combination to support students' learning [16].…”
Section: Category 2: Wiki Versus Google Docmentioning
confidence: 99%
“…Morley argues that the successful employment of Wiki requires careful guidance by the teacher as to how the Wiki works, or it may be helpful with face to face teaching combination to support students' learning [16]. On the contrary some literature suggests that Wiki encourages critical thinking, selfreflection, flexible environment for collaborative learning, and is consistent with constructivist and Vygotskian theories of learning [20]. It also helps to organize students' learning, allows them to learn from each other [17,18].…”
Section: Category 2: Wiki Versus Google Docmentioning
confidence: 99%
“…The effective use of wikis in the classroom has already been proven by earlier studies (Carr et al, 2007;Lundin, 2008;Olimpo et al, 2010). Wikis allow students to quickly and easily work together on texts (Lundin, 2008:434;Matthew, Felvegi & Callaway, 2009:51;Macdonald, 2008:154, 160;Olivier, 2011:123;Richardson, 2006:61, 65).…”
Section: Wikis As Instructional Toolmentioning
confidence: 99%
“…Kear, Woodthorpe, Robertson & Hutchison, 2010;Lundin, 2008;Olimpo, Davis, Lagman, Parekh & Shields, 2010;Ramanau & Geng, 2009). In South Africa Carr, Morrison, Cox and Deacon (2007) report on using a wiki for a final-year undergraduate political science course. However, the focus in these articles has been on collaborative writing as well as group work and not on the use of wikis to report on research undertaken by students or the use of a wiki as an instrument of peer assessment, as used in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike those studies, in our context the introduction of web-based learning necessitated substantial changes in all aspects of the activity system. The changes of the object described in the studies reported on in our review focused typically on one aspect of teaching and learning, for example on teacher team work (Kärkkäinen, 1999), conceptualization of students (Engeström et al, 2002a(Engeström et al, , 2202b, developing practices to help students with collaborative writing (Carr et al, 2007), professional development of both novices and experts (Tsui & Law, 2007), and collaborative forms of learning (Fåhraeus, 2004). …”
Section: Conclusion Implications and Limitationsmentioning
confidence: 99%